Defining the Potential of Nanoscale Re-Os Isotope Systematics Using Atom Probe Microscopy - Daly, L.; Bland, Phil; Tessalina, Svetlana; Saxey, David; Reddy, Steven; Fougerouse, Denis; Rickard, William; Forman, Lucy; La Fontaine, A.; Cairney, J.; Ringer, S.; Schaefer, B.; et al. (Wiley-Blackwell Publishing, 2018)
Atom probe microscopy (APM) is a relatively new in situ tool for measuring isotope fractions from nanoscale volumes (< 0.01 µm3). We calculate the theoretical detectable difference of an isotope ratio measurement result from APM using counting statistics of a hypothetical data set to be ± 4d or 0.4% (2s). However, challenges associated with APM measurements (e.g., peak ranging, hydride formation and isobaric interferences), result in larger uncertainties if not properly accounted for. We evaluate these factors for Re-Os isotope ratio measurements by comparing APM and negative thermal ionisation mass spectrometry (N-TIMS) measurement results of pure Os, pure Re, and two synthetic Re-Os-bearing alloys from Schwander et al. (2015, Meteoritics and Planetary Science, 50, 893) [the original metal alloy (HSE) and alloys produced by heating HSE within silicate liquid (SYN)]. From this, we propose a current best practice for APM Re-Os isotope ratio measurements. Using this refined approach, mean APM and N-TIMS187Os/189Os measurement results agree within 0.05% and 2s (pure Os), 0.6–2% and 2s (SYN) and 5–10% (HSE). The good agreement of N-TIMS and APM187Os/189Os measurements confirms that APM can extract robust isotope ratios. Therefore, this approach permits nanoscale isotope measurements of Os-bearing alloys using the Re-Os geochronometer that could not be measured by conventional measurement principles.